Spiritual Message of Al-Qur'an Calligraphy in Raudhatul Mukhlisin Mosque Jember - Firdausiyah, Umi Wasilatul; Wafi, Hasan Abdul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2022)
The discourse of this research lies in the presence of calligraphy on the walls of the Raudhatul Mukhlisin mosque, Jember Regency with mosque congregations. The discourse of this research lies in the existence of calligraphy on the walls of the Raudhatul Mukhlisin mosque, Jember Regency, with the mosque's congregation. This paper aims to find out the existence of calligraphy in the spirituality of the congregation in the Raudhatul Mukhlisin mosque, Jember Regency. They were assisted by using the type of phenomenological research with data collection techniques with observation, in-depth interviews, and documentation. The results of this study are that the existence of calligraphy, which can be said to be luxurious at the Raudhatul Mukhlisin mosque, not only gives a feeling of amazement, peace when looking at it and a calm heart when worshiping, but there are some jam'ah who feel disturbed when worshiping at the mosque because of its focus. Divided by calligraphy on the mosque walls has an attraction to be seen during worship. In conclusion, the existence of calligraphy on the walls of the Raudhatul Mukhlisin mosque seeks to introduce religion through calligraphy and aesthetics. In conclusion, the existence of calligraphy on the walls of the Raudhatul Mukhlisin mosque seeks to introduce religion through calligraphy and aesthetics.